Essays on capital structure and investment of non-financial firms: an international comparison - Usman, Ahmed (2018)
This doctoral thesis investigates various capital structure and investment decisions of non-financial firms when (i) banks of the firms become riskier after the Global Financial Crisis (ii) firms operate in countries with heterogeneous financial architecture i.e. bank-oriented and market-oriented countries and (iii) firms face increased macroeconomic uncertainty after the crisis. We also treat Global Financial Crisis of 2007 as an exogenous shock to the supply of capital and investigate the impact of the crisis on different financing and investment decisions of non-financial firms. We examine the cross section of the firms and investigate the differential behaviour of higher growth firms (as measured by Tobin's Q). The central finding of this thesis is that financial architecture is one of the most important determinants of capital structure and investment decisions of non-financial firms. When higher growth firms operating in market-oriented countries face an increase in the market riskiness of banks after the crisis, these firms do not suffer a decrease in overall leverage and the level of investment. These higher growth firms in market-oriented countries also have lower cost of debt and higher intensive and extensive margins of bond financing. Finally, the probability of bank loans and equity (bonds) issuance decrease (increase), after an increase in the downside macroeconomic uncertainty after the crisis. We carefully control firm’s demand for credit using various proxies, therefore all our results point towards supply side effect of credit.